On some potential ghost words in Baltic - Jakob, Anthony (Baltistica, 2023)
In this paper, I discuss five words in the East Baltic languages which have a dubious history. (1) Lithuanian kẽmeras ‘hemp agrimony’ has entered the standard language through botanical literature and derives ultimately from Nesselmann’s incorrect interpretation of an obsolete kiemerai ‘demon(s), incubus’; (2) sálti ‘to flow’ is known only from a single quotation deriving from K. Jaunius. It seems just as possible to interpret it semantically as ‘to creep’ and therefore as related to Lithuanian selė́ti ‘to creep’. Other forms attributed to this root also permit alternative interpretations; (3) bãlas ‘white’ is known only from Juška’s dictionary, where it may represent a rationalization of bãlas ‘anemone’. Only the latter can independently be verified from Žemaitian sources; (4) uodẽgis ‘fox’, often quoted in the Germanicist literature, results from a misinterpretation of the gloss given in Kurschat’s dictionary. Furthermore, uodẽgis ‘Fuchsschwänzer’ seems, in turn, to derive from Nesselmann’s misreading of Mielcke’s dictionary; (5) both Latvian īls ⟨ihls⟩ and ikls ‘stockfinster’ trace back to a lost manuscript dictionary by Fürecker; one is almost certainly an error, and it is further tempting to interpret ikls as an error for the otherwise attested akls ‘blind, pitch dark’.